Demographic studies and constraints of buffalo farming in East Godavari district of Andhra Pradesh - B.V.V. Satyanarayana Rao; A. Anitha; Jagadeeswara Rao; B. Subrahmanyeswari (Journal of Veterinary and Animal Sciences, 2022)
A survey was conducted to analyse the buffalo farming system in East Godavari district of Andhra Pradesh. The demographic studies showed that 77 per cent of buffalo farmers in the study area were of middle age. Majority of buffalo milk producers in delta and upland areas belonged to other caste, but in agency area, most belonged to scheduled tribe. Buffalo farmers under the survey were educated (52.67%) and agriculture was their occupation supported by dairying. Buffalo farmers in agency area practiced agriculture, horticulture and dairying whereas in delta and upland area practiced only agriculture and dairying. Majority of milk producers in delta area were small farmers and in upland area were marginal farmer category. Most (83.67%) of the families were of small size (up to 4 members) in the study area. Upland milk producers had more extension contact with veterinarians (53%). Most (83.67%) of the milk producers had no exposure to mass media. Inadequate availability of fodder seed/ slipswas the major constraint perceived by the milk producers of study area. Veterinarians expressed problem of anestrous or silent heat and repeat breeding in buffaloes as major constraints in dairy production in East Godavari district.